2020
DOI: 10.3390/toxins13010020
|View full text |Cite
|
Sign up to set email alerts
|

The Anemonia sulcata Toxin BDS-I Protects Astrocytes Exposed to Aβ1–42 Oligomers by Restoring [Ca2+]i Transients and ER Ca2+ Signaling

Abstract: Intracellular calcium concentration ([Ca2+]i) transients in astrocytes represent a highly plastic signaling pathway underlying the communication between neurons and glial cells. However, how this important phenomenon may be compromised in Alzheimer’s disease (AD) remains unexplored. Moreover, the involvement of several K+ channels, including KV3.4 underlying the fast-inactivating currents, has been demonstrated in several AD models. Here, the effect of KV3.4 modulation by the marine toxin blood depressing subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…In the present study we showed that limonene, acting on ROS production, prevented the K V 3.4 current enhancement induced by Aβ 1-42 oligomers. Of note, the increase in ROS level observed in AD is recognized to be an early biochemical event leading to the enhancement of K V 3.4 currents induced by Aβ 1-42 oligomers [32,36,40]. Therefore, consistent with our previous results, we hypothesized that a marked increase in ROS levels observed here may produce the upregulation of K V 3.4 activity also in primary cortical neurons.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study we showed that limonene, acting on ROS production, prevented the K V 3.4 current enhancement induced by Aβ 1-42 oligomers. Of note, the increase in ROS level observed in AD is recognized to be an early biochemical event leading to the enhancement of K V 3.4 currents induced by Aβ 1-42 oligomers [32,36,40]. Therefore, consistent with our previous results, we hypothesized that a marked increase in ROS levels observed here may produce the upregulation of K V 3.4 activity also in primary cortical neurons.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, in other studies K V 3.4 is reported to be an oxidation-sensitive channel since it is directly modulated by ROS increasing K V 3.4 current amplitude [41]. Importantly, we observed that K V 3.4 silencing or pharmacological inhibition with the sea anemone toxin blood depression substance-I (BDS-I) prevented Aβ 1-42 -induced insults in neurons as well as abnormal Ca 2+ signaling and ER stress in astrocytes [36,40]. Strikingly, in vivo silencing of K V 3.4 was able to reduce glial fibrillary acidic protein (GFAP) over-expression and Aβ 1-42 trimer burden in the Tg2576 mice brain, a transgenic model of AD [32].…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations